Magnetic interactions of 4f electrons in the topological insulator chalcogenide Bi2Se3 - Souza, J. C.; Carlone, M. [UNESP]; Lesseux, G. G.; Pizzi, H. B.; Freitas, G. S.; Urbano, R. R.; Venegas, P. A. [UNESP]; Pagliuso, P. G. (American Physical Society (APS), 2022)
The gap-opening mechanism of a topological insulator, the quantum anomalous Hall effect, and the axion physics are still pressing open questions, and a microscopic viewpoint to further understand the role of magnetism in topology is highly desirable. In this work we have performed a microscopic investigation, by means of electron spin resonance (ESR) along with complementary bulk measurements, on the chalcogenide (Bi1-xGdx)2Se3 (x=0, 0.001, 0.002 and 0.006). Our analysis of the Gd3+ spin dynamics reveals no significant change of the Fermi surface as a function of Gd3+ concentration, which indicates that the 4f magnetism is different from the nonlocal effects induced by transition metal (d electrons) substitutions. Additionally, we observe an unusual evolution of the Gd3+ ESR spectra as a function of the applied magnetic field, which we discuss considering the magnetic interaction between Gd3+4f electrons and impurity centers such as Se vacancies. This interaction would give rise to a local weak antilocalization effect surrounding the Gd3+ ions. Such a mechanism is observable due to particular details of the Gd3+4f electrons' magnetism in this system compared to that of d electrons. Our work points out that rare-earth substitutions in this model topological insulator are a promising path to explore the axion insulating systems.